Effect of phosphorus and sulphur levels on soil nutreint status in sunflower (Helianthus annuus L.): Effect of phosphorus and sulphur levels on soil nutreint status in sunflower (Helianthus annuus L.) - MD FARHAT KOUSAR; P A VISALAKSHI DEVI; A AZIZ QURESHI; T VENKATA SRIDHAR (Journal of Oilseeds Research, 2023)
A field experiment was conducted to study the response of Sunflower to Phosphorus and Sulphur levels at Agricultural College Farm, Bapatla, during rabi, 2018. The experiment was laid out in randomized block design with factorial concept replicated thrice with ten treatments. The Phosphorus and Sulphur status in soil increased with increasing levels of phosphorus from 0 to 135 kg P2O5 ha-1 but significant upto 90 kg P2O5 ha-1 whereas, the highest level of sulphur i.e., 30 kg S ha-1 recorded significantly higher uptake of Phosphorus and Sulphur soil at all growth stages of Sunflower.